Molecular Basis and Emerging Strategies for Anti-aging Interventions (Springer Singapore, 2018)
This book describes the nature of aging, age-related disorders, and the molecular principles of emerging strategies for anti-aging interventions, while also discussing the discovery of targets for geroprotective drugs. Although significant medical advances in the treatment and eradication of life-threatening conditions such as cardiovascular and infectious disease have been made over the past five decades, the prevalence of age-related disorders still remains high in older populations. Intervening into aging is the next frontier in contemporary medicine, and will be of increasing importance over time, as other sources of poor health are combated more and more successfully. Given the universal interest in anti-aging strategies, the book will appeal to a very broad audience. It addresses a diverse range of anti-aging interventions - including stem cells, autophagy, senolytics, anti-inflammatory methods, and telomerase induction - that will be of interest to scientists and researchers from various disciplines in the life sciences. .